Online Dating and the Risk of Sexual Assault to College Students - Scannell, Meredith Jean (Building Healthy Academic Communities Journal, 2019)
Background: Advances in technology have created different platforms, such as online dating, where college students can meet other people. One serious risk factor of using online dating is the risk of sexual assault. Many sexual predators will use online dating as a method to connect with potential victims who are often vulnerable and trusting. Aim: This paper discusses the risk of sexual assault among college students who use online dating sites. Faculty can be pivotal in educating students on the dangers of online dating and sexual assault. In addition, faculty members are in a position to recognize signs students may be exhibiting after a sexual assault, offer advice, and provide linkage to necessary services. Results: Risk factors of sexual assault are explored in depth, including predatory tactics and the vulnerability specific to college students. Provided are key safety tips for online dating as well as recommendations regarding resources and reporting to law enforcement. Conclusions: Online dating is popular among college students. Educating students in safety factors will enable them to consider the potential dangers and risk of sexual assault. In addition, higher education institutions must consider the needs of students and provide links to resources, support systems and reporting mechanisms.